PERANAN TOKOH MASYARAKAT DALAM PENANGANAN MASALAH SENGKETA TANAH DI DESA SULU KECAMATAN TATAPAAN KABUPATEN MINAHASA SELATAN - Rembang, Prisilia; Lasut, Jouke J.; Kandowangko, N. (Universitas Sam Ratulangi, 2018)
Land problems can give rise to a legal dispute which originated from a complaint something parties (persons/entities) contain objections or demands for land rights, be it the status of land or rights of ownership with the hope of obtaining administrative resolution in accordance with the applicable provisions. The case or the conflict over land occurring almost throughout Indonesia. The observations indicate that there is a land dispute shows almost the same pattern, different cases of land disputes concerning the fate of the people was almost entirely takes a fairly long and long process complete.The methods used in this study i.e., qualitative descriptive. Methods of qualitative research procedures that produce as data in the form of descriptive words written or spoken of people and behavior that can be observed.The problem of land disputes in the village of Tatapaan Sub-district of Sulu became protracted because of the inability of the Government to resolve problems due to lack of mastery of the Government and community leaders on the issue of the right of land ownership According to the custom of the land changed hands frequently and by way of the purchases under the hands, not the full data of the soil that is on the register of the land Office at book village of Sulu Tatapaan Sub Regency of Minahasa in the South.Â Keywords: land disputes, settlement, Government